The envelope protein of SARS‐CoV‐2 increases intra‐Golgi pH and forms a cation channel that is regulated by pH. (24th March 2021) - Cabrera‐Garcia, David; Bekdash, Ramsey; Abbott, Geoffrey W.; Yazawa, Masayuki; Harrison, Neil L.
Abstract : Key points: We report a novel method for the transient expression of SARS‐CoV‐2 envelope (E) protein in intracellular organelles and the plasma membrane of mammalian cells and Xenopus oocytes. Intracellular expression of SARS‐CoV‐2 E protein increases intra‐Golgi pH. By targeting the SARS‐CoV‐2 E protein to the plasma membrane, we show that it forms a cation channel, viroporin, that is modulated by changes of pH. This method for studying the activity of viroporins may facilitate screening for new antiviral drugs to identify novel treatments for COVID‐19. Abstract: The envelope (E) protein of coronaviruses such as SARS‐CoV‐1 is proposed to form an ion channel or viroporin that participates in viral propagation and pathogenesis. Here we developed a technique to study the E protein of SARS‐CoV‐2 in mammalian cells by directed targeting using a carboxyl‐terminal fluorescent protein tag, mKate2. The wild‐type SARS‐CoV‐2 E protein can be trafficked to intracellular organelles, notably the endoplasmic reticulum–Golgi intermediate complex, where its expression increases pH inside the organelle. We also succeeded in targeting SARS‐CoV‐2 E to the plasma membrane, which enabled biophysical analysis using whole‐cell patch clamp recording in a mammalian cell line, HEK 293 cells, and two‐electrode voltage clamp electrophysiology in Xenopus oocytes. The results suggest that the E protein forms an ion channel that is permeable to monovalent cations such as Na +, Cs + and K + . The E current is nearly time‐ and voltage‐independent when E protein is expressed in mammalian cells, and is modulated by changes of pH. At pH 6.0 and 7.4, the E protein current is activated, whereas at pH 8.0 and 9.0, the amplitude of E protein current is reduced, and in oocytes the inward E current fades at pH 9 in a time‐ and voltage‐dependent manner. Using this directed targeting method and electrophysiological recordings, potential inhibitors of the E protein can be screened and subsequently investigated for antiviral activity against SARS‐CoV‐2 in vitro and possible efficacy in treating COVID‐19. Key points: We report a novel method for the transient expression of SARS‐CoV‐2 envelope (E) protein in intracellular organelles and the plasma membrane of mammalian cells and Xenopus oocytes. Intracellular expression of SARS‐CoV‐2 E protein increases intra‐Golgi pH. By targeting the SARS‐CoV‐2 E protein to the plasma membrane, we show that it forms a cation channel, viroporin, that is modulated by changes of pH. This method for studying the activity of viroporins may facilitate screening for new antiviral drugs to identify novel treatments for COVID‐19.